Differences in Story Facts in the Translated Text of Lontar Yusup and Serat Nabi Yusuf - Rakhmi, Martina Puspita; Doyin, Mukh; Setyaningsih, Nas Haryati (Universitas Negeri Semarang, 2023)
Narrative facts are elements that serve as imaginative records of a story, including characters (figures and traits), plot, and setting. This research aims to analyze the differences in narrative facts in the translated texts of “Lontar Yusup” and “Serat Nabi Yusuf”. The research approach used is objective, and data collection utilizes structural techniques. The research data sources are the book by Wiwin Indiarti, “Lontar Yusup Banyuwangi: Teks Pegon – Transliterasi – Terjemahan” (2018), and the book by Laela Nurhayati Dewi and Hermawati titled “Serat Nabi Yusuf: Transkripsi dan Transliterasi” (2011). Data analysis is conducted using structural reading techniques. The research findings reveal differences in the character aspect, including differences in the main characters influenced by differences in the central narrative focus, the mentioning of character names that refer to the names and character details, character actions that affect the details of the characters' traits, character dialogues that refer to the choice of words used and the purpose of the dialogue, and the feelings/thoughts of the characters. Differences in the exposition and complication aspects of the plot include details in the plot and the addition of scenes, such as added character actions, differences in character actions, and the addition of reasons for character actions. Differences in the setting aspect are only found in time and place.